The evolution of patient-focused drug development and Duchenne muscular dystrophy. (2nd January 2020) - Crossnohere, Norah L.; Fischer, Ryan; Crossley, Emily; Vroom, Elizabeth; Bridges, John FP
ABSTRACT: Introduction: There is a groundswell of interest from patient, industry, and regulatory groups to rigorously and transparently integrate patient-voice into regulatory decision-making. Patient-focused drug development (PFDD) is an approach established by the US Food and Drug Administration to systematically incorporate patient experiences into drug development and evaluation. It has created a demand for scientific advancement to measure and integrate patient-voice into decision-making. Areas covered: This narrative review describes the evolving nature of advocacy-regulatory relations preceding PFDD, characterizes current PFDD and other patient-engagement activities, and explores future opportunities for patient participation along the drug development pipeline. We present Duchenne muscular dystrophy as a case study to illustrate how PFDD is being operationalized by patient groups and regulators using both verbal and written data sources. Expert opinion: PFDD represents the most widespread approach yet to integrate the patient voice as a source of evidence to inform regulatory decision-making. Regulatory approvals are just one frontier in drug development. On the horizon remain uncertainties in how patient experience can inform post-marketing surveillance, pricing, reimbursement, and health technology assessment. Patient-input may be particularly crucial to demonstrate the value of expensive first-generation rare disease treatments that confer meaningful benefits but do not meet traditional thresholds for cost-effectiveness.